Developing a Mathematical Equation to Predict Khums and Zakat in the Iranian Economy - Nader Namdar; Mehdi Moradi; Yaghoub Mohmodian; Mehdi Sadegi Shahdani; Roghayieh Hassanzadeh (Center of Strategic Studies (PUSKAS) BAZNAS, 2021)
Khums and Zakat in Islam, especially among Shiite communities, are the most important religious aspects for establishing the Islamic economy, so the accurate prediction of their amount is significant to ensure the provision, planning and financial targeting in the Islamic economy. The purpose of this descriptive-exploratory study is to fit the calculations made of Khums and potential Zakat in the country during the years 2008 to 2014 and design a mathematical equation to predict the amount of Khums and potential Zakat in the Islamic economy of Iran, using the second-degree equation of Fourier Series in MATLAB software. While calculating the types of Khums and Zakat, the research results determine the coefficient of determination R2 equal to 1 for total Khums, 0.9982 for income Khums, 0.9838 for total Zakat, 0.991 for Zakat without livestock and 0.9203 for total Khums and total Zakat. The results are obtained from the mean base square of RMS are 0, 0, 1.2504, 1.503 and 1.4982, and the adjusted coefficient of adjusted R2 are 0, 0, 0.9029, 0.2947 and 0.5215, respectively. It is a sign of the goodness of accurate fitting of research calculations. In this article, for each of the five types of Khums and Zakat, the formula for calculating the output of specific coefficients are recorded and presented by MATLAB software, which is an efficient method in predicting results in other sciences and can predict the types of Khums and Zakat in the Islamic economy of Iran accurately.